2016
DOI: 10.1371/journal.pone.0165659
|View full text |Cite
|
Sign up to set email alerts
|

Immunodominant IgM and IgG Epitopes Recognized by Antibodies Induced in Enterovirus A71-Associated Hand, Foot and Mouth Disease Patients

Abstract: Enterovirus A71 (EV-A71) is one of the main causative agents of hand, foot and mouth disease (HFMD). Unlike other enteroviruses that cause HFMD, EV-A71 is more frequently associated with severe neurological complications and fatality. To date, no effective licensed antivirals are available to combat EV-A71 infection. Little is known about the immunogenicity of viral non-structural proteins in humans. Previous studies have mainly focused on characterization of epitopes of EV-A71 structural proteins by using imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…The N‐terminal half of VP1 protein also induced a poly‐reactive anti‐enterovirus IgG response . The well‐reported anti–EV‐A71 IgG epitopes SP70 and VP2‐28, identified by mice and rabbit sera respectively, were not recognized by human sera, suggesting that human sera target different linear or discontinuous conformational epitopes compared with animal sera . Nonetheless, all the identified immunogenic epitopes in humans or animals induced neutralizing activities, suggesting the importance of neutralization responses during EV‐A71 infection …”
Section: Host Immune Responses To Ev‐a71 Infectionmentioning
confidence: 99%
“…The N‐terminal half of VP1 protein also induced a poly‐reactive anti‐enterovirus IgG response . The well‐reported anti–EV‐A71 IgG epitopes SP70 and VP2‐28, identified by mice and rabbit sera respectively, were not recognized by human sera, suggesting that human sera target different linear or discontinuous conformational epitopes compared with animal sera . Nonetheless, all the identified immunogenic epitopes in humans or animals induced neutralizing activities, suggesting the importance of neutralization responses during EV‐A71 infection …”
Section: Host Immune Responses To Ev‐a71 Infectionmentioning
confidence: 99%
“…10 We recently also showed that even at high dilutions, acutely-infected patient sera with EV-A71-specific IgM antibody responses had high neutralization titers. 11 These findings suggest that IgM is particularly important for virus neutralization during acute EV-A71 infection. To examine this, we (Table 1).…”
Section: Resultsmentioning
confidence: 90%
“…On the VP2 protein, only anti‐EV‐A71 IgM epitopes were recognized within the VP2 neutralization epitope, vp2‐50 (148‐159: YKQTQPGADGFE) . We recently also showed that even at high dilutions, acutely‐infected patient sera with EV‐A71‐specific IgM antibody responses had high neutralization titers . These findings suggest that IgM is particularly important for virus neutralization during acute EV‐A71 infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations